Investigation of 46 cases of eosinophilic otitis media - Matsubara, Atsushi; Sato, Mami; Nomura, Ayami; Fujita, Tomoaki; Fukuoka, Yu; Takahata, Junko; Matsushita, Daisuke; Itoga, Masamichi; Kudo, Reiko (Journal of Immunology, Allergy and Infection in Otorhinolaryngology, 2024)
Eosinophilic otitis media (EOM) is a type of refractory otitis media characterized by middle ear discharge with marked eosinophilic infiltration. The diagnostic criteria were developed approximately 20 years ago, but there are still only a few reports concerning the actual treatment for EOM at present. In this report, we investigated patient background and treatment given and its effect on EOM patients treated in our department for the past 5 years.The subjects included 82 ears of 46 patients treated in our department between January 1, 2017 and November 1, 2022. Thirty-seven patients had coexisting bronchial asthma (BA) and 28 patients had coexisting chronic rhinosinusitis (CRS). Twenty-six cases were associated both BA and CRS, while only seven cases were not associated with either. Concerning treatment, almost all cases were given second-generation antihistamines, in addition to antileukotrienes and ibudilast. Biologics were introduced as treatment for eosinophilic chronic rhinosinusitis (ECRS) or BA and showed improvement in the otitis media severity score. The use of biologics, including dupilumab, are also effective in the treatment for EOM, indicating the importance of systemic therapeutic intervention, along with the use of local treatments.